MUZIUM SEBAGAI INSTRUMEN PENDIDIKAN BUDAYA WARISAN : SUATU KAJIAN KES DI MUZIUM ADAT, JELEBU, NEGERI SEMBILAN - MUHAMMAD AZRI, MUHAMMAD SUHAIMI (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study is about the cultural heritage of educational instruments used by the Customs Museum. The study focuses on the establishment and management methods in the context of the cultural heritage organization and content of the exhibition gallery. The study was carried at Customs Museum and the Jelebu area. The results of this study, the study used qualitative and quantitative methods of observation, interviews and distributing questionnaires to organizations Customs Museum and the surrounding population. According to the findings, the Customs Museum is a place to record history and educates the public about cultural heritage education. The method used by the Customs Museum is a showcase of the latest and various activities for the community. There are four galleries in the Museum of Indigenous and storyline designed by Prof. Nor Halim.